Produksi Karkas dan Non Karkas Domba Priangan dan Ekor Gemuk pada Bobot Potong 17,5 dan 25,0 Kg - R Herman (Faculty of Animal Science, Bogor Agricultural University, 2005)
Carcass and non-carcass production of Priangan and Fat Tail sheep were studied at the Department of Animal Production, Faculty of Animal Science, Bogor Agricultural University. Six male Priangan and six male Fat Tailed lambs were killed at 17.5 kg slaughter weight. A similar number of both breeds were also killed at 25.0 kg. Priangan and Fat Tail of 18.483 ± 0,160 and of 18.583 ± 0.262 kg body weight were fasted 24 hours (water was allowed) and fasted body weight (slaughter weight) were 17.600 ± 0.089 and 17.490 ± 0.020 kg, respectively. Similarly, Priangan and Fat Tail of 26.190 ± 0.207 and 26.283 ± 0.349 kg were also fasted at the same treatment and slaughter weights were 24.914 + 0.183 and 24.890 ± 0.114 kg. Before killing, they were reared on a pelleted ration containing 73.3% TDN and 16% crude protein (100% dry matter basis). Those animals were killed and dissected. The results showed that there were no significant differences in the weight of carcass, organs and offals, except in the weight of head and tail at 17.5 kg (P < 0.05) and at 25.0 kg (P < 0.01). At 17,5 kg slaughter weight, Priangan (17600 ± 89 g) produced 47.10% carcass, 11.14% head and shank, 6.67% skin, 14.38% offals, 4.84% blood and 12.71% gut content; Fat Tail (17490 ± 20 g) produced 48.76% carcass, 9.20% head and shank, 7.00% skin, 13.38% offals, 4.08% blood and 11.99% gut content. At 25.0 kg slaughter weight, Priangan (24917 ± 183 g) produced 48.70% carcass, 10.14% head and shank, 6.90% skin, 12.90 offals, 5.03% blood and 12.12% gut content. Fat Tail produced 52.39% carcass, 8.39% head and shank, 7.00% skin, 13.11% offals, 4.19% blood and 10.61% gut content. Key words: Priangan sheep, carcass